Phenome-wide association of APOE alleles in the All of Us Research ProgramResearch in context - Ehsan Khajouei; Valentina Ghisays; Ignazio S. Piras; Kiana L. Martinez; Anthony T. Vicenti; Marcus Naymik; Preston Ngo; Tam C. Tran; Joshua C. Denny; Travis J. Wheeler; Matthew J. Huentelman; Eric M. Reiman; et al. (EBioMedicine)
Summary: Background: Apolipoprotein E (APOE) variation is associated with altered lipid metabolism, as well as cardiovascular and neurodegenerative disease. Prior studies are largely limited to European ancestry populations and differential risk by sex and ancestry has not been widely evaluated. Methods: We utilised a phenome-wide association study (PheWAS) to explore APOE-associated phenotypes in the All of Us Research Program. We determined APOE alleles for 181,880 participants, representing seven ancestry groups. We tested association of APOE variants, ordered based on Alzheimer’s disease risk hierarchy (ε2/ε2 < ε2/ε3 < ε3/ε3 < ε2/ε4 < ε3/ε4 < ε4/ε4), with 2318 phenotypes. Bonferroni-adjusted analyses were performed overall, by ancestry, by sex, and with adjustment for social determinants of health (SDOH). Findings: In the overall cohort, PheWAS identified 17 significant associations, including increased odds of hyperlipidaemia (OR 1.15 [1.14–1.16] per APOE genotype group; P = 1.8 × 10−129), dementia, and Alzheimer’s disease (OR 1.55 [1.40–1.70]; P = 5 × 10−19), and reduced odds of fatty liver disease and chronic liver disease. ORs were similar after SDOH adjustment and by sex, except for an increased number of cardiovascular associations in males, and decreased odds of noninflammatory disorders of vulva and perineum in females. Significant heterogeneity was observed for hyperlipidaemia and mild cognitive impairment across ancestry. Unique associations by ancestry included transient retinal arterial occlusion in the European ancestry group, and first-degree atrioventricular block in the American Admixed/Latino ancestry group. Interpretation: We replicate extensive phenotypic associations with APOE alleles in a large, diverse cohort. We provide a comprehensive catalogue of APOE-associated phenotypes and evidence of unique phenotypic associations by sex and ancestry, as well as heterogeneity in effect size across ancestry. Funding: Funding is listed in the Acknowledgements section.